G195(P) Adverse Events and Datix Incident Reporting in Paediatrics. (7th April 2014) - Braha, NH; Raine, J; Bennett, L; Abrol, E; Chambers, WG; Gabrel, M; Collins, L
Abstract : Aims: The Francis report (2013) described a failure to listen to patients and staff, a tolerance of clinical risk and a lack of inter-agency communication. Recently, the Datix reporting system has been introduced at our hospital. We aimed to analyse reported incidents and to explore reporting practices in the Paediatric Department. Methods: Datix reports submitted between July 2009 and October 2012 were analysed. Staff were subsequently asked to complete an anonymous questionnaire. Results: 785 reports were submitted (19.6 per month). The majority involved young children: 32% involved a child under 1 year and 24% involved a child between 1 and 5 years. Most incidents occurred on the General Paediatric ward (59%), followed by the Neonatal Intensive Care Unit (19%) and the Paediatric Emergency Department (18%). 71% of incidents were clinical, 60% of which were medication errors. The majority reported were 'low' or 'medium' risk, only 4% were 'high' risk. A few (13%) led to an adverse outcome, including 12 clinical deteriorations, 6 Emergency Department re-attendances and one recall to hospital. 54 of the 57 questionnaires were returned (95% response rate). Four were incomplete and therefore excluded. Respondents included doctors (42%), nurses (38%), administrative staff (10%), healthcare assistants and play specialists (10%). Perceptions of reporting practices varied: 50% of nurses stated that incidents were always reported but only 5% of doctors said this was the case. Datix data indicated that 70% of reports were submitted by nurses with only 13% being submitted by doctors. Importantly, 60% of participants admitted to never having reported an incident on Datix. Reasons for under-reporting included time pressures, software issues, concerns about anonymity and a perception that reporting was futile. Respondents requested software alterations and training and feedback on the incidents reported. Conclusion: Clinical incidents, particularly medication errors, are frequent. Serious incidents are rare. Despite the introduction of the Datix system, there appears to still be significant under-reporting. To reduce medication errors, electronic prescribing has been introduced. Datix training has been incorporated into the Trust induction and junior doctors reporting incidents are routinely asked to complete a Datix form.